2017
DOI: 10.3389/fmicb.2017.01637
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility among Urban Wastewater and Wild Shellfish Isolates of Non-O1/Non-O139 Vibrio cholerae from La Rance Estuary (Brittany, France)

Abstract: The early 2000s marked the end of the Golden age of the antibiotics and the beginning of the awareness on the potential threat to human health due to the dissemination of antimicrobial resistance. As a base-line study, we investigated the antimicrobial susceptibility of 99 strains of non-O1/non-O139 Vibrio cholerae isolated from wastewater and shellfish in 2000/2001 within La Rance estuary (Brittany, France). All isolates were susceptible to amoxicillin-clavulanic acid, cefotaxime, imipenem, chloramphenicol, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 64 publications
7
33
0
2
Order By: Relevance
“…In the current study, results also found isolates of significant health importance that show high degree of multidrug resistance and analysis of the MAR index of isolates showed that most of the isolates had MARI of >0.2, this serves as a pointer to high use of antibiotics in such environments. The high rates of resistance by these isolates in this study agreed with the previous studies [42,[49][50][51][52]. These isolates should raise concern as they play role in many hospital infections.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, results also found isolates of significant health importance that show high degree of multidrug resistance and analysis of the MAR index of isolates showed that most of the isolates had MARI of >0.2, this serves as a pointer to high use of antibiotics in such environments. The high rates of resistance by these isolates in this study agreed with the previous studies [42,[49][50][51][52]. These isolates should raise concern as they play role in many hospital infections.…”
Section: Discussionsupporting
confidence: 91%
“…This study recorded 58% susceptibility level with 29% resistance to ampicillin. This compared favorably with other studies which exhibiting resistance to ampicillin [61,80,81]. Furthermore, Igbinosa, [12] and Quilici et al, [71] reported intermediate susceptibility to ampicillin while Ismail et al, [63] and Tran et al, [67] reported high susceptibility level to ampicillin from Vibrio cholera tested in South Africa and Vietnam.…”
Section: Discussionsupporting
confidence: 69%
“…22,23 Many NOVC stains have been isolated in the coastal waters of countries such as Germany, India, South Korea, and France. [24][25][26][27] Our review found that 47.8% of patients (11/23) had a possible source of infection; 6 cases were attributed to consuming seafood and 4 to contaminated water. Two cases presented swelling or pain in the lower leg after contact with contaminated water through a wound.…”
Section: Mode Of Transmissionmentioning
confidence: 87%